2019
DOI: 10.3390/su11164382
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Introducing Climate-Change Adaptation in Pavement Management

Abstract: Greenhouse gas emissions have caused global temperatures to rise since the mid-20th century accompanied by sea-level rise (SLR). Temperature increases and SLR-induced groundwater rise have been shown to cause premature pavement failure in many roadway structures. Hybrid bottom-up/top-down (hybrid) adaptation approaches have shown promise by initially investigating an asset’s response to incremental environmental change and then identifying the timing of critical effects for budgetary planning. This improves pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Moreover, clients' procedures when managing maintenance projects during the long life cycle of a transport infrastructure system may strongly influence sustainability aspects. For example, these procedures may both directly affect everyday lives of many people, and the environmental impact arising from factors such as use of heavy machinery and asphalt [58,59]. Another major reason for selecting the focal case was that it involved a collaborative business arrangement that has not been previously applied in Sweden.…”
Section: Research Design and Case Backgroundmentioning
confidence: 99%
“…Moreover, clients' procedures when managing maintenance projects during the long life cycle of a transport infrastructure system may strongly influence sustainability aspects. For example, these procedures may both directly affect everyday lives of many people, and the environmental impact arising from factors such as use of heavy machinery and asphalt [58,59]. Another major reason for selecting the focal case was that it involved a collaborative business arrangement that has not been previously applied in Sweden.…”
Section: Research Design and Case Backgroundmentioning
confidence: 99%
“…They concluded that variabilities in precipitation and, thus, in soil moisture, can reduce road design reliability, although the climate change signal may be minimal in terms of precipitation. Similar studies were also conducted for the USA, Canada, and Egypt [68][69][70][71][72][73].…”
Section: Quantitative Assessment Methodsmentioning
confidence: 54%
“…In the past decade, a number of researchers have looked for ways to tweak pavement parameters to better combat the fluctuating climate conditions. Temperature, precipitation, incoming percent of sunshine, humidity, wind speed, and groundwater levels are the climate factors that alter pavement performance, design, and service life (Knott et al 2019a). In addition, the other factors such as permafrost thaw, freezing index, and freeze and thaw cycles significantly influence the flexible pavement in the Northern part of Canada (Maadani et al 2021).…”
Section: Climate Change and Its Impactmentioning
confidence: 99%